Development of omni-direction shear-horizontal wave magnetostrictive transducer for NDE applications - Ho, Adele Wan Qi (Nanyang Technological University, 2023)
Non-destructive evaluation (NDE) is to be used to inspect a material for flaws. One of the methods of NDE is ultrasonic testing and it can detect in-depth flaws of most materials, as long as they can conduct sound. The concept of ultrasonic testing is whereby ultrasonic transducers convert various types of energy into ultrasonic vibrations, which will be further converted into electrical signals via an oscilloscope. With different types of ultrasonic transducers, this project focuses on magnetostrictive transducers and aims to develop the transducer such that it can operate omni-directionally using shear horizontal waves. Using steel and aluminum plates to conduct experiments for omni-directionality, five different transducers are used. These transducers are different in the case of them having different sizes coils or multiple rounds of winding. The experiments are then conducted to determine which size of coil and how many rounds of coil winding should be used to maximize the performance of the transducer. A total of 10 transducer results are shown in a viewable graph depicting the amplitude of the received waves at each 12 points. It is then concluded from the results that one round of coil winding is the most optimal and that a thick coil of 0.4mm is preferred.